Safety and efficacy of calcipotriol plus betamethasone dipropionate gel in the treatment of scalp psoriasis in adolescents 12–17 years of age. (1st December 2014) - Gooderham, M.; Debarre, J.‐M.; Keddy‐Grant, J.; Xu, Z.; Kurvits, M.; Goodfield, M.
Summary: Background: Plaque psoriasis has a relatively high prevalence in adolescence, resulting in a significant impact on quality of life, including social interactions. Objectives: The primary objective was to assess the safety of once‐daily application of fixed‐combination calcipotriol plus betamethasone dipropionate gel in adolescent scalp psoriasis. Assessment of efficacy was a secondary objective. Methods: This phase II, multicentre, single‐arm, open‐label, 8‐week trial included patients aged 12–17 years with moderate‐to‐very severe scalp psoriasis according to Investigator's Global Assessment (IGA) (≥ 10% of the scalp area affected). Results: Seventy‐eight patients received treatment. Twenty‐seven patients (35%) reported a total of 64 adverse events (AEs); most were mild (33/64) or moderate (22/64) in severity and there were no serious AEs. No cases of hypercalcaemia were reported, and the mean changes from baseline to end of treatment in albumin‐corrected serum calcium (0·00 mmol L −1 ), 24‐h urinary calcium excretion (−0·03 mmol per 24 h) and urinary calcium‐to‐creatinine ratio (−0·12 mmol g −1 ) were not considered clinically relevant. At the end of treatment 66 patients (85%) were clear or almost clear according to IGA. There was an 80% improvement in mean Total Sign Score from baseline to end of treatment. In total, at the end of treatment, 87% of patients rated their scalp psoriasis as clear or very mild, and 75 (96%) had no or mild pruritus compared with 14 (18%) at baseline. Conclusions: Once‐daily calcipotriol plus betamethasone dipropionate gel is well tolerated and efficacious for scalp psoriasis in adolescents.